Urgensi Mendongeng dalam Membangun Budaya Membaca pada Anak : Analisis Terhadap Ayat-Ayat al-Qur’an tentang Berkisah - Syaifur Rohman (DIMAR: Jurnal Pendidikan Islam, 2022)
Children are the most valuable assets in human life, even the state, nation and religion that must be maintained, guided, and directed so that they can grow and develop properly. Giving role modes for children is very important but no less important is to provide as much information as possible for children so that it can be used as a foundation for children in the future, because that is the key to success in the child's education stage is how to provide as much information as possible to children, one of which is by technique. storytelling (storytelling). This technique is very closely related to culture in Indonesia, how history in Indonesia is conveyed by way of speech from adults to their children. For this reason, it is necessary to revitalize storytelling techniques in people's lives today. Not only as a means of forming a noble personality, story telling is a way to pass on a literacy culture to children. Given the low literacy culture in Indonesia, a solution is needed, namely by excavating the treasures of local wisdom that characterize the community. This article is based on an analysis of the verses of the Qur'an about storytelling techniques which are even used as one of the ways in the Qur'an to provide lessons for mankind. The Qur'an gives a signal about the importance of the hearing aspect in the educational process through the qishah technique as well as signifies the importance of providing information by providing news that is conveyed to humans, because the sense of hearing is the first sense that is active in human growth and development. With this basis, to cultivate a reading culture in a child, a child can use storytelling or storytelling techniques so that a literacy culture is gradually formed within the child which can be used as a foundation when they are adults.